2017
DOI: 10.1016/j.amsu.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Long term efficacy of extracorporeal shock wave therapy [ESWT] for treatment of refractory chronic abacterial prostatitis

Abstract: ObjectiveTo evaluate the effect and safety of extracorporeal shockwave therapy (ESWT) on chronic pelvic pain syndrome (CPPS)/chronic abacterial prostatitis after failure of most other modalities of treatment, the maintenance of the treatment effect for up to one year post treatment and whether the patients are in need for further sessions.Materials and methodsIn a follow-up survey of 41 patients, the study inclusion criteria were CPPS patients who failed at least previously 3 modalities of treatment other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 18 publications
4
54
1
4
Order By: Relevance
“…Clinical trials on the safety and efficacy profile of LiESWT in treating female SUI are still not completely clear. Clinically, LiESWT has emerged in recent years to treat (1) chronic pelvic pain syndrome (CPPS) (0.10-0.25 mJ/ mm 2 , 3000 pulses, once/week, 4 weeks) to improve pain, bladder voiding and QoL 17,[24][25][26][27] ; (2) erectile dysfunction (ED) (0.10-0.25 mJ/mm 2 , 3000-6000 pulses, once/week, 4-8 weeks) to increase penile hemodynamics and induce penile tissue regeneration 18,28,29 . In this study, the recruited subjects had normal BMI, blood pressure, renal function, liver function, blood sugar level, and lipid profiles, thus eliminating the potential confounding factors ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on the safety and efficacy profile of LiESWT in treating female SUI are still not completely clear. Clinically, LiESWT has emerged in recent years to treat (1) chronic pelvic pain syndrome (CPPS) (0.10-0.25 mJ/ mm 2 , 3000 pulses, once/week, 4 weeks) to improve pain, bladder voiding and QoL 17,[24][25][26][27] ; (2) erectile dysfunction (ED) (0.10-0.25 mJ/mm 2 , 3000-6000 pulses, once/week, 4-8 weeks) to increase penile hemodynamics and induce penile tissue regeneration 18,28,29 . In this study, the recruited subjects had normal BMI, blood pressure, renal function, liver function, blood sugar level, and lipid profiles, thus eliminating the potential confounding factors ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ESWT has been investigated in CPPS due to its anti-inflammatory, analgesic, and anti-spastic effects. The previous studies showed that ESWT is an effective modality and is safe for the treatment of CPPS 12 , 13 , 14 , 15 , 16 , 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…80 Previous studies have shown that LESW has protective effects on inflammatory reaction, by lowering the expression of NGF, IL-6, IL-12, TNF-a, COX-2 and iNOS. 67 82 There were no significant side-effects in these studies (Table 1). However, more trials with different protocols to maximize the short-and long-term outcome are required before LESW can be widely applied in non-bacterial prostatitis/CPPS.…”
Section: Inflammatory Disorders: Non-infectious Prostatitis or Cystitismentioning
confidence: 73%
“…Al Edwan et al . further demonstrated the maximal effects of LESW (ESWT once a week for 1 month, with a protocol of 2500 pulses on the perineum with total energy flow density 0.25 mJ/mm 2 over 13 min) on the IPSS, NIH‐CPSI and the American Urological Association Quality of Life due to Urinary Symptoms scale at 2 weeks; the effect was stabilized until 12 months . There were no significant side‐effects in these studies (Table ).…”
Section: Rationale For Using Lesw In the Lower Urinary Tractmentioning
confidence: 77%